2005
DOI: 10.1002/cbic.200400422
|View full text |Cite
|
Sign up to set email alerts
|

An Inverse Substrate Orientation for the Regioselective Acylation of 3′,5′‐Diaminonucleosides Catalyzed by Candida antarctica lipase B?

Abstract: Abstract. Candida antarctica lipase B (CAL-B

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 52 publications
2
23
1
1
Order By: Relevance
“…It was proposed that there exists a hydrophobic interaction between the propyl group of acyl chain and the hydrophobic side (C 5 -C 6 -R 1 ) of the thymine in the conformation of the 5Ј-butanoylation of β-thymidine. [12] According to the model, the 5Ј-regioselectivity should increase with an enhancement of the hydrophobicity of the R 1 group. However, we found that the 5Ј-selectivity did not increase, but decreased in waved form with enhancing hydrophobicity of the R 1 group (Table 1, Entries 1-5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was proposed that there exists a hydrophobic interaction between the propyl group of acyl chain and the hydrophobic side (C 5 -C 6 -R 1 ) of the thymine in the conformation of the 5Ј-butanoylation of β-thymidine. [12] According to the model, the 5Ј-regioselectivity should increase with an enhancement of the hydrophobicity of the R 1 group. However, we found that the 5Ј-selectivity did not increase, but decreased in waved form with enhancing hydrophobicity of the R 1 group (Table 1, Entries 1-5).…”
Section: Resultsmentioning
confidence: 99%
“…The molecular modeling has revealed that the C2Ј atom lies above the medium-sized pocket in the conformation of the 5Ј-acylation transition state, whereas it fits into the medium-sized pocket in the conformation of the 3Ј-acylation. [12] X-ray crystallographic studies have shown that the medium-sized pocket, into which the sugar moiety binds, has not enough room for a substituent larger than the propyl group. [9,12] As a result, the presence of the R 2 group as a hydroxy group might cause a steric clash and destabilize the conformation of the 3Ј-acylation transition state, thus enhancing the 5Ј-regioselectivity and decreasing the reaction rate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account the scarcity of computer modelling studies about the aminolysis reaction, 15 we used this tool to rationalise the great differences of reactivity and enantioselectivity shown by CAL-B towards these cycloalkanamines. In recent years, molecular modelling has been successfully used to explain both the mechanism of action and the substrate selectivity of lipases.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason we modelled a phosphonamidate 15 ( Figure 2A) as an analog of the tetrahedral intermediate TI-2 resulting from the attack of the amine to the carbonyl of the acyl-enzyme. This intermediate is the equivalent to the phosphonate analogs successfully employed in the molecular modelling studies on the transesterification of alcohols.…”
Section: Resultsmentioning
confidence: 99%